A comparative study of spark plasma sintered TiCx-Ni3Ti/Ni cermets. (April 2018) - Liu, Bolu; Huang, Shuigen; Van Humbeeck, Jan; Vleugels, Jef
Abstract: Ni3 Ti intermetallic has a high chemical and structural stability as well as strength at elevated temperature. It can be potentially used as a binder for TiC based cermets. In the present study, TiC0.8 -14.7 vol% Ni3 Ti and TiC0.95 -14.7 vol% Ni cermets were prepared by spark plasma sintering from a TiC0.95 -NiTi and -Ni powder mixture respectively, and investigated in terms of sintering behavior, microstructure and mechanical properties. The results revealed that a fully dense Ni3 Ti binder cermet with a homogeneous binder distribution was obtained after sintering for 4 min at 1100 °C, whereas a dense Ni binder cermet was obtained after sintering for 10 min at 1240 °C. The better sinterability of the Ni3 Ti binder cermet could be explained based on calculated ternary phase diagrams. The Ni3 Ti and Ni binder cermet exhibited a similar titanium carbide grain size (2.8 ± 0.4 μm and 2.2 ± 0.5 μm, respectively). The E-modulus, hardness and bending strength of the Ni3 Ti binder cermet were lower than for the Ni binder cermet, whereas the fracture toughness was higher. Highlights: Fully dense TiCx -Ni3 Ti/Ni cermets are obtained after spark plasma sintering. The sinterability of the Ni3 Ti binder cermets is better than for the Ni binder cermets. The toughness of the Ni3 Ti binder cermets is higher than for the Ni binder cermets. The Ni3 Ti and Ni binder cermets fracture inter- and transgranularly respectively.